The prevalence of sarcopenic obesity and its association with cognitive performance in type 2 diabetes in Singapore. Issue 7 (July 2020) - Low, Serena; Goh, Kiat Sern; Ng, Tze Pin; Ang, Su Fen; Moh, Angela; Wang, Jiexun; Ang, Keven; Subramaniam, Tavintharan; Sum, Chee Fang; Lim, Su Chi
Summary: Background & aims: We aim to examine body composition, and association between SO and cognitive performance in Type 2 Diabetes (T2D) in an Asian population in Singapore. Methods: This was a cross-sectional study on 1235 patients with mean age 61.4 ± 8.0 years and T2D primary and secondary care attending diabetes care in Singapore. Body composition was assessed using tetrapolar multi-frequency BIA device analysis. Fat mass to fat-free mass (FM/FFM) ratio was categorized into 3 groups: Group 1, normal, <0.40; Group 2, obese and increase of FM is small relative to that in FFM, 0.40 to 0.80; and Group 3, SO, >0.80. Cognition was assessed using Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and Mini-Mental State Examination (MMSE). Results: The distribution of body composition based on FM/FFM ratio was: Group 1, 20.2%; Group 2, 60.5%; and Group 3, 19.4%. SO (Group 3) was significantly associated with reduced RBANS total score with β-1.44 (95%CI -2.82 to −0.06; p = 0.041) in multivariable linear regression adjusted for demographics, education, depressive symptom(s) and clinical covariates. SO was significantly associated with reduced index scores for immediate memory and language in fully adjusted models with corresponding βs −2.71 (95%CI -5.06 to −0.36; p = 0.024) and −2.48 (95%CI -4.87 to −0.08; p = 0.043). Association between SO and reduced MMSE score was similarly observed. Conclusions: The prevalence of SO in Asians with T2D is relatively high. There is consistent and independent association of SO with reduced cognitive performance, especially in domains of memory and language, which may impair complex executive function such as adherence to diabetes self-care management. Highlights: The prevalence of sarcopenic obesity (SO) in Asians with T2D is relatively high. SO is independently associated with reduced cognitive performance. The association is observed in domains of memory and language.